2007
DOI: 10.4012/dmj.26.451
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Release of Simvastatin Acid Using Cyclodextrin Inclusion System

Abstract: Simvastatin acid (SVA) has been reported to stimulate bone formation by increasing expression of BMP-2 in osteoblasts. Due to their multi-functional characteristics and bioadaptability, cyclodextrins (CDs) are capable of forming inclusion complexes with many drugs by including a whole drug molecule inside their cavity. In the present study, we prepared SVA/CD inclusion complex solutions with different pH values. These were then used to determine their SVA release behavior after coating on titanium substrates, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…Brushite cements have a high ionic concentration and an acidic setting reaction, properties that could reduce or inhibit the action of certain drugs [7]. Nevertheless, a previous study concluded that the therapeutic action of simvastatin was not altered after being released by a brushite cement [23], which could be partially explained by the stability of simvastatin in acidic pHs [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brushite cements have a high ionic concentration and an acidic setting reaction, properties that could reduce or inhibit the action of certain drugs [7]. Nevertheless, a previous study concluded that the therapeutic action of simvastatin was not altered after being released by a brushite cement [23], which could be partially explained by the stability of simvastatin in acidic pHs [31].…”
Section: Discussionmentioning
confidence: 99%
“…n. 79902-63-9, USA) was used as the model drug. Whereas lipophilic molecules of simvastatin (lactone) are metabolized in the liver for the reduction of cholesterol, a more hydrophilic form (hydroxyacid) is needed in hard tissues applications to potentiate its pharmacological effect [30,31]. The simvastatin was therefore hydrolysed to convert its isolated β-hydroxyacid form into an open ring by adding the simvastatin in an alkaline solution of ethanol/NaOH 0.1 M and heating it at 50 ºC for 2 h [32].…”
Section: Cement Preparationmentioning
confidence: 99%
“…Simvastatin is administered by gavage and requires hepatic conversion to metabolically active β-hydroxy acid to become medicinally active. Therefore, for local administration, simvastatin must first be hydrolyzed to form simvastatin acid 18,19) . The structure of fluvastatin is significantly different from those of previously used HMG-CoA reductase inhibitors such as the pravastatin and simvastatin metabolites, which are derived from fungi 20,21) .…”
Section: Discussionmentioning
confidence: 99%
“…23) Simvastatin is administered by gavage and requires hepatic conversion to metabolically active â-hydroxy acid to become medicinally active. Therefore, for local administration, simvastatin would first have to be hydrolyzed to simvastatin acid 24,25) . In this experiment, fluvastatin was used to investigate the effect of the local administration of statins.…”
Section: Discussionmentioning
confidence: 99%